HISTORICAL AND GEOGRAPHICAL TERMS IN TEXTBOOKS FOR THE LOWER GRADES OF PRIMARY SCHOOL – FOUNDATION FOR THE LOCALISATION OF EPIC POEMS - Cvetanović, Zorica; Blagdanić, Sanja; Dobrosavljević, Nikoleta (Metodička teorija i praksa, 2025)
The horizontal link between the contents of two school subjects, Serbian Language and Science and Social Studies, can be made by a broader localisation of literary works which places literary texts in social and historical contexts. The aim of this paper is to investigate whether the sets of Serbian Language textbooks and Science and Social Studies textbooks for the fourth grade of primary school are complementary in terms of providing students with a basis for understanding historical and geographical terms necessary for the localization and understanding of traditional epic poetry. Content analysis of textbooks published by nine publishing houses was carried out, using historical and geographical terms in the poem "Miloš u Latinima" аs a unit of the content analysis.There are 53 historical and geographical terms in this poem and they were classified into three categories – historical terms (personalities, rulers’ titles, other concepts from the past), geographical terms (settlements, rivers, mountains) and historical-geographical terms (nations, monasteries). The research results indicate that historical and geographical terms in the poem exist in the methodological apparatus of the textbooks and that there is a correlation in terms of the presence of these concepts in textbook sets of the same publisher for both school subjects. However, there is a level of inconsistency between the textbooks of the same publisher regarding the explanations of historical/geographical terms – some terms or concepts in the poem are either not explained in any of the textbooks or they are duplicated. It is necessary to find a way for harmonising the cross-curricular contents in the textbooks for a more successful localisation of traditional epic poems.